2007
DOI: 10.1590/s0074-02762007000800009
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired antibodies to merozoite surface protein (MSP)-1(19) and cumulative exposure to Plasmodium falciparum and Plasmodium vivax in remote populations of the Amazon Basin of Brazil

Abstract: To infer recent patterns of malaria transmission, we measured naturally acquired IgG antibodies to the conserved 19-kDa C-terminal region of the merozoite surface protein (MSP)-1 of both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
(30 reference statements)
5
11
0
3
Order By: Relevance
“…A seroprevalence of 46.9% for PvMSP-1 19 was reported and the probability of a positive IgG specific response was 3.44 times higher in individuals older than 15 years in comparison to those younger. Similar results were described by Ladeia-Andrade et al [27] across two sectional surveys conducted among 594 endemic residents (both children and adults) from riverine communities along the Jau and Unini rivers (Amazonas State). Anti-PvMSP-1 19 was positive in 69.6%, half way through the rainy season, and 64.0% at the middle of the dry season.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A seroprevalence of 46.9% for PvMSP-1 19 was reported and the probability of a positive IgG specific response was 3.44 times higher in individuals older than 15 years in comparison to those younger. Similar results were described by Ladeia-Andrade et al [27] across two sectional surveys conducted among 594 endemic residents (both children and adults) from riverine communities along the Jau and Unini rivers (Amazonas State). Anti-PvMSP-1 19 was positive in 69.6%, half way through the rainy season, and 64.0% at the middle of the dry season.…”
Section: Resultssupporting
confidence: 88%
“…This systematic review corroborates those findings describing an association between PvMSP-1 19 /PfMSP-1 19 and malaria exposure parameters (age, time of residence in endemic areas, and number of previous malaria episodes) in cross-sectional sero-epidemiological studies [24, 2729]. Although the gene sequences of MSP-1 19 antigens are exclusive to each Plasmodium species, considerable homology has been reported among them [51] and, therefore, cross-reactivity in co-endemic areas could be expected.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In Brazil, field studies have shown two principal types of malaria outcomes: The so-called "frontier malaria," which affects mainly nonimmune migrants which settle in gold mining or logging camps, exposing themselves to malaria infection (Sawyer, 1986;Camargo et al, 1994) and mild, often non-symptomatic infection (Alves et al, 2002;da Silva-Nunes and Ferreira, 2007;Ladeia-Andrade et al, 2007), mainly found in stable riverine and rural populations. Although quantitative long-term studies designed as described for example by Roussilhon et al (2007) are not available, not at least because of the relatively low and seasonal incidence of falciparum malaria, it seems that the dynamics of malarial infection and severity differ greatly from typical African settings such as found in Ghana or lowland Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…A imunogenicidade das diferentes regiões da PvMSP-1 tem sido estudada desde a década de noventa, com o intuito de se identificar uma região da molécula que desencadeie imunidade protetora. Após estudos iniciais da estrutura primária da PvMSP-1 identificando regiões conservadas e variáveis (Del Portillo, 1991) e sua imunogenicidade (Mancilla et al, 1994), estudos subseqüentes mostraram que a porção N-terminal (ICB2-5) é pouco reconhecida em infecções naturalmente adquiridas (Soares et al, 1997), enquanto a região conservada C-terminal (MSP-1 19 ) é bastante imunogênica Soares et al, 1997;Fraser et al, 1997;Soares et al, 1999a;Park et al, 2001;Nogueira et al, 2006;Barbedo et al, 2007;Ladeia-Andrade et al, 2007, Zeirek et al, 2008. Embora usando uma porção distinta da região N-terminal que inclui apenas parte do antígeno recombinante ICB2-5 utilizado por outros autores, nossos dados confirmam o baixo reconhecimento humoral da região não-conservada da PvMSP-1, bem como da alta imunogenicidade da região conservada C-terminal.…”
Section: Resultsunclassified